The light-dependent alteration in carbonic anhydrase activity in leaves of Crassula ovata (Crassulaceae) - Topchiy N.M.; Zolotareva O.K.; Dadyka V.V.; Fediuk O.M.; Onoiko O.B. (Ukrainian Botanical Journal)
Carbonic anhydrase, CA (EC 4.2.1.1), is the second most abundant protein in leaves of higher plants after ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCO), which is represented by three different families. CA plays a pivotal role in supplying CO₂ to RuBisCO and facilitating the hydration of CO2 to form HCO3−, which is then utilized as a substrate for phosphoenolpyruvate carboxylase (PEPC) in C4- and CAM-plants. Despite the pivotal role of CA in CAM-photosynthesis, there is a paucity of data on its isoforms, activity, and localization in CAM-plants. The objective of this study was to identify and characterize the forms of CA and to determine the level and distribution of CA activity among the soluble proteins of leaves in model CAM-plant Crassula ovata adapted to darkness and light. The level of CA activity in the fraction of soluble proteins varied from 30 to 85 WAU/mg protein depending on the time of day when leaf samples were collected. A notable decline in CA activity in the total leaf fraction of soluble proteins was observed during the transition from the dark to the light phase. A single isoform of the enzyme with a molecular mass of 29 kDa was identified in the extract from leaves of "light" C. ovata using electrophoretic separation in the presence of sodium dodecyl sulfate after visualization of CA activity by protonography. Two high molecular weight protein complexes exhibiting CA activity were detected in "light" and "dark" leaves by native electrophoresis and protonography methods. The hydratase activity of these complexes in dark-adapted leaves was significantly lower, compared to light-adapted ones. The data obtained indicate a light-dependent alteration in CA activity and its localisation in leaves of C. ovata during the "day-night" cycle.